The Effect of Key Opinion Leader, Instagram, and Digital Campaign through Brand Image on Brand Awareness in Evoria Products - Hasanudin; Amanda Risky Amalia (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Technology has brought major changes to human civilization, with almost everyone using technology in their daily lives, such as communicating through social media, shopping through e-commerce, and searching for information via the internet. This study uses the Amos Structural Equation Model method to examine the relationship between Key Opinion Leaders, Instagram, Digital Campaign, Brand Image, and Brand Awareness. The results of the study show that Key Opinion Leaders, Instagram, Digital Campaign, Brand Image, and Brand Awareness have a significant direct influence on Brand Image. With the increasing use of Key Opinion Leaders by Evoria, the company's Brand Image has also increased. The same applies to the use of Instagram and Digital Campaign, this study confirms that Brand Image has a direct and significant influence on Brand Awareness. These findings show the importance of Evoria to pay attention to and increase the use of Key Opinion Leaders, Instagram, and Digital Campaigns in an effort to build a strong Brand Image and Brand Awareness.